Identifying high ability students: a contribution from neuropsychological indicators - Dora Cortat Simonetti; Leandro S. Almeida; Zenita Guenther (Universidade Federal de Santa Maria (UFSM), 2010)
This paper presents some data on the convergence between psychometric intelligence measurements (IQ tests) and physiological signs of mental activity found in high ability adolescents. The research study focus on a small group of 15 subjects submitted to electric encephalograms, previously chosen from a larger group of 77 classmates on the basis of scores on the WISC-III IQ Test. The results suggest continuous predominance of Alpha waves for the gifted group (higher frequency percentile and higher amplitude) what was not observed in the group without any superior intellectual ability. Even taking into account methodological limitations, this study may contribute to the understanding of a relationship between the intellectual quotient (IQ) and alpha waves frequency and amplitude, as observed during performance on cognitive tasks. Such results may suggest a possibility to complement psychometric measures with encephalic registers in giftedness research studies.